Evaluating local first page university site using 'U' tool - Abd Aziz, Zalilah (2003)
Making a web site usable is necessary for a web-page to be successful and for users to be satisfied. Therefore, developing sites that are responsive to user needs is critical for all site designers and managers. With the increasing growth of e-learning and emphasis on higher education in our country, a good and usable university web sites are required for this demand. This project will focus at evaluating the usability characteristics of every first page of our local universities. The concentration of this project is to identify the proposed metrics and develop a prototype considering only the automated usability characteristics based on the ISO 9126 standard. Therefore, a prototype of 'U' tool is developed to serve this purpose